Perspektif Hukum Dalam Penanganan Pandemi Covid-19: Studi Komparatif di ASEAN-5 - Widiantoro, Andri; Astutik, Sri (Fakultas Syariah INSURI Ponorogo, 2023)
Literature regarding legal perspectives in handling Covid-19, especially with comparative studies between countries, is still small, so this study aims to analyze legal perspectives in handling the Covid-19 pandemic by applying comparative studies in ASEAN-5, namely Indonesia, Malaysia , Singapore, Thailand and the Philippines. This study uses normative legal research methods and comparative descriptions. The results of the study show that all countries focus on the health, social and economic recovery sectors.